2018
DOI: 10.1038/s41598-018-32723-5
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline and oxide phases revealed and formed on InSb(111)B

Abstract: Oxidation treatment creating a well-ordered crystalline structure has been shown to provide a major improvement for III–V semiconductor/oxide interfaces in electronics. We present this treatment’s effects on InSb(111)B surface and its electronic properties with scanning tunneling microscopy and spectroscopy. Possibility to oxidize (111)B surface with parameters similar to the ones used for (100) surface is found, indicating a generality of the crystalline oxidation among different crystal planes, crucial for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…For the (3 × 3)-reconstructed InSb(111)B surface, a currently accepted model is that proposed by Wever et al in 1994, where the reconstructed top layer was determined to be composed of three types of In-Sb hexamers: α, β, and γ rings, from their x-ray diffraction and STM analyses [61]. This model also reasonably agrees with other experimental observations [60,64,65]. These conclusions are generally consistent with our STM results in Fig.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…For the (3 × 3)-reconstructed InSb(111)B surface, a currently accepted model is that proposed by Wever et al in 1994, where the reconstructed top layer was determined to be composed of three types of In-Sb hexamers: α, β, and γ rings, from their x-ray diffraction and STM analyses [61]. This model also reasonably agrees with other experimental observations [60,64,65]. These conclusions are generally consistent with our STM results in Fig.…”
supporting
confidence: 91%
“…S2. An InSb(111)B surface can exhibit (3 × 3), (2 × 2), or (3 × 1) reconstruction, depending on the experimental conditions [58][59][60][61][62][63][64][65]. In our experiments, a smooth InSb(111) B surface is produced following an ultrahigh-vacuum (UHV) cleaning process (see Supplemental Material, Sec.…”
mentioning
confidence: 99%
“…[24d] Due to the oxophilic nature of In and Sb, bulk InSb oxidizes easily when exposed to air at room temperature, and stable In/Sb oxides quickly form on the surface of InSb. [25,26] The CQDs are more susceptible to oxidation, owing to their large surface-to-volume ratio. We observed the presence of In 2 O 3 and Sb 2 O x (x = 3 or 5) in assynthesized CQDs, as determined from X-ray photoelectron spectroscopy (XPS) analysis (Figures 1c and 1d).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the oxophilic nature of In and Sb, bulk InSb oxidizes easily when exposed to air at room temperature, and stable In/Sb oxides quickly form on the surface of InSb [25,26] . The CQDs are more susceptible to oxidation, owing to their large surface‐to‐volume ratio.…”
Section: Resultsmentioning
confidence: 99%
“…While many of the clean InSb surfaces have been imaged with STM [18][19][20][21][22][23][24][25][26][27][28][29][30] , there have been only a few studies on the surface electronic structure of InSb with STS 25,30,31 . Most STS studies of InSb have been on the cleaved (110) (1x1) surface 25,31 , which have demonstrated the cleaved surface can be unpinned and devoid of surface states within the semiconductor band gap.…”
Section: Introductionmentioning
confidence: 99%